Local Refractive Index Sensing Based on Edge Gold-Coated Silver Nanoprisms - Martinsson, Erik (2016)
Bulk and surface refractive index sensitivity for localized surface plasmon resonance (LSPR) sensing based on edge gold-coated silver nanoprisms (GSNPs) and gold nanospheres was investigated and compared with conventional surface plasmon resonance (SPR) sensing based on propagating surface plasmons. The hybrid GSNPs benefit from an improved stability since the gold frame protecting the unstable silver facets located at the silver nanoprisms (SNPs) edges and tips prevents truncation or rounding of their sharp tips or edges, maintaining a high refractive index sensitivity even under harsh conditions. By using layer-by-layer deposition of polyelectrolytes and protein adsorption, we found that GSNPs exhibit 4-fold higher local refractive index sensitivity in close proximity (<10 nm) to the surface compared to a flat gold film in the conventional SPR setup. Moreover, the sensitivity was 8-fold higher with GSNPs than with gold nanospheres. This shows that relatively simple plasmonic nanostructures for LSPR-based sensing can be engineered to outperform conventional SPR, which is particularly interesting in the context of detecting low molecular weight compounds where a small sensing volume, reducing bulk signals, is desired.